Thienopyrimidinone derivatives that inhibit bacterial tRNA (guanine37-N1)-methyltransferase (TrmD) by restructuring the active site with a tyrosine-flipping mechanism - Zhong, Wenhe (2021)
Among the >120 modified ribonucleosides in the prokaryotic epitranscriptome, many tRNA modifications are critical to bacterial survival, which makes their synthetic enzymes ideal targets for antibiotic development. Here we performed a structure-based design of inhibitors of tRNA-(N1G37) methyltransferase, TrmD, which is an essential enzyme in many bacterial pathogens. On the basis of crystal structures of TrmDs from Pseudomonas aeruginosa and Mycobacterium tuberculosis, we synthesized a series of thienopyrimidinone derivatives with nanomolar potency against TrmD in vitro and discovered a novel active site conformational change triggered by inhibitor binding. This tyrosine-flipping mechanism is uniquely found in P. aeruginosa TrmD and renders the enzyme inaccessible to the cofactor S-adenosyl-l-methionine (SAM) and probably to the substrate tRNA. Biophysical and biochemical structure-activity relationship studies provided insights into the mechanisms underlying the potency of thienopyrimidinones as TrmD inhibitors, with several derivatives found to be active against Gram-positive and mycobacterial pathogens. These results lay a foundation for further development of TrmD inhibitors as antimicrobial agents.